High shear stress amplitude in combination with prolonged stimulus duration determine induction of osteoclast formation by hematopoietic progenitor cells. Issue 3 (19th January 2020) - Bratengeier, Cornelia; Liszka, Aneta; Hoffman, Johan; Bakker, Astrid D.; Fahlgren, Anna
Abstract: To date, it is unclear how fluid dynamics stimulate mechanosensory cells to induce an osteoprotective or osteodestructive response. We investigated how murine hematopoietic progenitor cells respond to 2 minutes of dynamic fluid flow stimulation with a precisely controlled sequence of fluid shear stresses. The response was quantified by measuring extracellular adenosine triphosphate (ATP), immunocytochemistry of Piezo1, and sarcoplasmic/endoplasmic Ca 2+ reticulum ATPase 2 (SERCA2), and by the ability of soluble factors produced by mechanically stimulated cells to modulate osteoclast differentiation. We rejected our initial hypothesis that peak wall shear stress rate determines the response of hematopoietic progenitor cells to dynamic fluid shear stress, as it had only a minor correlation with the abovementioned parameters. Low stimulus amplitudes corresponded to activation of Piezo1, SERCA2, low concentrations of extracellular ATP, and inhibition of osteoclastogenesis and resorption area, while high amplitudes generally corresponded to osteodestructive responses. At a given amplitude (3 Pa) and waveform (square), the duration of individual stimuli (duty cycle) showed a strong correlation with the release of ATP and osteoclast number and resorption area. Collectively, our data suggest that hematopoietic progenitor cells respond in a viscoelastic manner to loading, since a combination of high shear stress amplitude and prolonged duty cycle is needed to trigger an osteodestructive response. Plain Language Summary: In case of painful joints or missing teeth, the current intervention is to replace them with an implant to keep a high‐quality lifestyle. When exercising or chewing, the cells in the bone around the implant experience mechanical loading. This loading generally supports bone formation to strengthen the bone and prevent breaking, but can also stimulate bone loss when the mechanical loading becomes too high around orthopedic and dental implants. We still do not fully understand how cells in the bone can distinguish between mechanical loading that strengthens or weakens the bone. We cultured cells derived from the bone marrow in the laboratory to test whether the bone loss response depends on (i) how fast a mechanical load is applied (rate), (ii) how intense the mechanical load is (amplitude), or (iii) how long each individual loading stimulus is applied (duration). We mimicked mechanical loading as it occurs in the body, by applying very precisely controlled flow of fluid over the cells. We found that a mechanosensitive receptor Piezo1 was activated by a low amplitude stimulus, which usually strengthens the bone. The potential inhibitor of Piezo1, namely SERCA2, was only activated by a low amplitude stimulus. This happened regardless of the rate of application. At a constant high amplitude, a longer duration of the stimulus enhanced the bone‐weakening response. Based on these results we deduce that a high loading amplitude tends to be bone weakening, and the longer this high amplitude persists, the worse it is for the bone.